2016
DOI: 10.4238/gmr.15037292
|View full text |Cite
|
Sign up to set email alerts
|

Association between TNF-α rs1800629 polymorphism and the risk of myocardial infarction: A meta-analysis

Abstract: ABSTRACT. The tumor necrosis factor-alpha (TNF-α) G-308A polymorphism has been suggested to be a susceptibility factor for myocardial infarction (MI). However, differing results from various studies have led to controversial conclusions. Hence, we performed a meta-analysis to evaluate the association between TNF-α G-308A polymorphism and MI. Reported studies published before March 30, 2015 were included and analyzed from the PubMed and Embase databases. Study selection and data extraction were carried out inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
4
0
4
Order By: Relevance
“…Results of the previously published studies were also variable regarding the association of the TNF-α -308 G>A genotype with the various diseased states. Linkage of the TNF-α AA genotype has been reported with the increased TNF-α expression, rheumatic heart disease, myocardial infarction and ischemic stroke [9,12,40]. On the contrary, a case–control study on North Indians revealed no association between TNF genotypes and T2DM [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the previously published studies were also variable regarding the association of the TNF-α -308 G>A genotype with the various diseased states. Linkage of the TNF-α AA genotype has been reported with the increased TNF-α expression, rheumatic heart disease, myocardial infarction and ischemic stroke [9,12,40]. On the contrary, a case–control study on North Indians revealed no association between TNF genotypes and T2DM [41].…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have provided evidence for the association of the single nucleotide promoter polymorphism of TNF-α and IL-6 with the severity of the disease process in Met S while others are non-conclusive [9–11]. A systematic meta-analysis by Hua et al [12] reported significant association of TNF-α -308 promoter polymorphism with the stages of myocardial infarction in Caucasians and Asians. However, no significant association of TNF-α promoter polymorphism with coronary artery disease and myocardial infarction was found in a case–control study on the Han Chinese population [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ген TNF расположен в локусе 6p21.3 в регионе генов главного комплекса гистосовместимости III класса. Уровень белка ФНО-α зависит от полиморфизма промоторного региона гена, наиболее часто изучаемыми вариантами являются G-238A (rs361525), G-308A (rs1800629) и C-857T (rs1799724) [26]. Самым изученным является rs1800629: установлена зависимость от генотипов -308 G/А экспрессии гена как на уровне мРНК, так и белкового продукта в плазме крови, что связано с изменением активности промотора [27].…”
Section: клеточно-молекулярные основы постинфарктного по вреждения сеunclassified
“…Так, например, в работе Biswas S, et al (2014) у носителей генотипа AA rs1800629 в гене TNF концентрация сывороточного уровня ФНО-α была значимо выше и ассоциировалось с ИМ с подъемом сегмента ST [21]. Тем не менее, результаты таких исследований в отношении ИМ в целом нередко противоречивы: в одних исследованиях ассоциация подтверждается [28], в других -нет [26]. В ряде исследований выявлено наличие ассоциаций только у мужчин, например, в исследовании Tian M, et al (2015) показано, что генотип -308AA TNF является рисковым для развития ОИМ у мужчин, но не у женщин [23].…”
Section: клеточно-молекулярные основы постинфарктного по вреждения сеunclassified
See 1 more Smart Citation